Bioaccumulation and Mapping Heavy Metals of Lead (Pb) in Turbinaria sp in Teluk Kodek, Pemenang, North Lombok - Lala karunia lisna Illah; Moh Awaludin Adam; Nurul Izzati (Indonesian Society of Limnology, 2023)
Pollution of the aquatic environment can come from domestic, agricultural and industrial activities. The waters of the Teluk Kodek were suspected of being polluted by the activities of waste fuel dumped by ship moorings. This study aims to analyze lead (Pb) contamination in the waters of the Teluk Kodek and to map the distribution of Pb in Turbinaria Sp. This research method is the collection of water samples, substrate and Turbinaria Sp in the waters of the Teluk Kodek with three replications. The heavy metal content of Pb was tested using the Atomic Absorption Spectrophotometer (AAS), and then the data was processed by analysis of variance (ANOVA). At the same time, they are mapping the distribution of Pb in Turbinaria Sp using Scanning Electron Microscopy (SEM). The results showed that the waters of the Teluk Kodek had experienced accumulation of the heavy metal Pb in the substrate samples and Turbinaria Sp. While the results of water samples are still below the threshold. Mapping the distribution of Pb in the Turbinaria Sp sample shows the distribution results in each part of the sample. It is necessary to carry out early pollution prevention activities in the waters of the Teluk Kodek so that the aquatic environment remains sustainable.